Burden of NCDs, Policies and Programme for Prevention and Control of NCDs in India - R K Srivastava; D Bachani (Wolters Kluwer Medknow Publications, 2011)
Noncommunicable diseases and injuries account for 52% of deaths in India. Burden of noncommunicable diseases and resultant mortality is expected to increase unless massive efforts are made to prevent and control NCDs and their risk factors. Based on available evidence, cancer, diabetes, hypertension, cardiovascular diseases, stroke, chronic obstructive pulmonary disease, chronic kidney disease, mental disorders and trauma are the leading causes of morbidity, disability and mortality in India. Government of India had supported the States in prevention and control of NCDs through several vertical programs since 1980s. However, during the 11 th plan, there was considerable upsurge to prevent and control NCDs. New programs were started on a low scale in limited number of districts. However, there has not been any considerable change in the burden of NCDs. Based on experiences in the past, there is need to emphasize on health promotion and preventive measures to reduce exposure to risk factors. Facilities and capacity for screening, early diagnosis and effective management are required within the public health care system. Public awareness program, integrated management and strong monitoring system would be required for successful implementation of the program and making services universally accessible in the country.